Analisis Pertumbuhan Ekonomi dan Ketimpangan Pendapatan : Data Panel 8 Provinsi di Sumatera - Khairul Amri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2017)
This study aims to determine the causality relationship between economic growth and income inequality. Using panel data of 8 provinces in Sumatera during the period of 2007-2015. The data analyzed by panel vector autoregression (PVAR) and panel granger causality test. The study found that economic growth over a given period was significantly influenced by the economic growth of the previous year, and income inequality over a given year was also significantly influenced by the income inequality of the previous year. The result of panel granger causality test found that there is unidirectional causality from income inequality to economic growth.